2011
DOI: 10.1159/000329307
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Preservation in Heterotopic Cervical Pregnancy: What Is the Best Procedure?

Abstract: We describe a patient who underwent assisted reproduction techniques and was diagnosed with heterotopic cervical pregnancy, and then discuss the management of this entity, which is rare and has no standard protocols. Treatment consisted of intra-arterial methotrexate (50 mg/m2 body surface area) and simultaneous selective embolization of uterine arteries. The literature is also reviewed to identify other approaches and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Treatment of cervical ectopic pregnancy is one of the most problematic issues in the area of early gestational complications. Because of historical narratives associating surgical treatment of CEP with maternal morbidity and mortality, non‐surgical approaches have been sought, and preferred where available . For this purpose, MTX, which is an anti‐metabolite drug known for its ability to kill trophoblastic cells, has been used in the treatment of CEP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of cervical ectopic pregnancy is one of the most problematic issues in the area of early gestational complications. Because of historical narratives associating surgical treatment of CEP with maternal morbidity and mortality, non‐surgical approaches have been sought, and preferred where available . For this purpose, MTX, which is an anti‐metabolite drug known for its ability to kill trophoblastic cells, has been used in the treatment of CEP.…”
Section: Discussionmentioning
confidence: 99%
“…Because of historical narratives associating surgical treatment of CEP with maternal morbidity and mortality, non-surgical approaches have been sought, and preferred where available. [7][8][9]12 For this purpose, MTX, which is an anti-metabolite drug known for its ability to kill trophoblastic cells, has been used in the treatment of CEP. MTX was first used in the treatment of CEP by Farabow et al 10 Subsequent studies showed that that the drug was safe and efficient, [13][14][15][16][17] but dose, schedule and follow-up protocols are yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many protocols to administrate MTX for cervical pregnancy . We presented four cases successfully managed by transcatheter MTX injection into bilateral uterine arteries without embolization.…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades with the advent of transvaginal sonography, which can facilitate an earlier diagnosis, conservative management is therefore more commonly practiced. A variety of approaches have been proposed,10 including dilation and evacuation combined with Foley balloon tamponade, methotrexate with/without KCL injection, uterine artery embolisation4 12 and ligation of cervical branches of uterine arteries. The most commonly reported medical treatments are methotrexate, either local injection (intra-amniotic or intrafetal)1 13 14 or systemic administration,2 3 7 9 15–17 commonly used in conjunction with fetal KCL injection 15 18.…”
Section: Discussionmentioning
confidence: 99%